Exposure to Atomic Bomb Radiation and Age-Related Macular Degeneration in Later Life: The Hiroshima-Nagasaki Atomic Bomb Survivor Study - Itakura, Katsumasa; Takahashi, Ikuno; Nakashima, Eiji; Yanagi, Masahide; Kawasaki, Ryo; Neriishi, Kazuo; Wang, Jie Jin; Wong, Tien Yin; Hida, Ayumi; Ohishi, Waka; Kiuchi, Yoshiaki (Investigative ophthalmology & visual science, 2015)
To investigate the association between radiation exposure from the atomic bombings and the prevalence of age-related macular degeneration (AMD) among older residents of Hiroshima and Nagasaki. The Adult Health Study is a cohort study of atomic bomb survivors living in Hiroshima and Nagasaki, comprising 2153 participants who underwent examinations with retinal fundus photographs in 2006-2008. The radiation dose to the eye for the analysis was estimated with the revised dosimetry system (DS02). The retinal photographs were graded according to the Wisconsin Age-Related Maculopathy Grading System modified for nonstereoscopic retinal images. Early and late AMD were defined according to the type of lesion detected in the worse eye of the participants. Person-specific data were analyzed by using a logistic regression model to assess the association between radiation dose and AMD. Among the 1824 subjects with gradable retinal images (84.7% of the overall participants), the estimated eye dose was widely distributed, with a mean of 0.45 Gy and standard deviation of 0.74 Gy. The prevalence of early and late AMD was 10.5% and 0.3%, respectively. There were no significant associations between radiation dose and AMD, with each 1-Gy increase in exposure, adjusted odds ratio was 0.93 (95% confidence interval [CI], 0.75-1.15) for early AMD and 0.79 (95% CI, 0.21-2.94) for late AMD. No significant associations were found between atomic bomb irradiation early in life and the prevalence of early or late AMD later in life among Japanese atomic bomb survivors.